2021
DOI: 10.21037/apm-21-1218
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine attenuates cerebral ischemia-reperfusion injury in rats by inhibiting the JNK pathway

Abstract: Background: Cerebral ischemic reperfusion injury (CI/RI) is a common cerebrovascular disease with high morbidity and disability that threatens human health. This study was conducted to explore the effects of dexmedetomidine (Dex) on the c-Jun N-terminal kinase (JNK) pathway in CI/RI, and to provide a theoretical basis for the recovery of brain function after cerebral ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…After administering dexmedetomidine, the PSD95–NR2B–nNOS interaction was decreased efficiently, and they found dexmedetomidine could enhance cognitive and motor recovery following TBI [ 9 ]. Another study showed that dexmedetomidine can alleviate cerebral ischemic reperfusion injury in rats by increasing the α2-adrenergic receptor and blocking JNK phosphorylation and the activation of caspase-3 [ 10 ]. Feng’s study showed that dexmedetomidine improves neurological outcomes in mice and reduces neuronal death by protecting against neural autophagy and neuroinflammation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After administering dexmedetomidine, the PSD95–NR2B–nNOS interaction was decreased efficiently, and they found dexmedetomidine could enhance cognitive and motor recovery following TBI [ 9 ]. Another study showed that dexmedetomidine can alleviate cerebral ischemic reperfusion injury in rats by increasing the α2-adrenergic receptor and blocking JNK phosphorylation and the activation of caspase-3 [ 10 ]. Feng’s study showed that dexmedetomidine improves neurological outcomes in mice and reduces neuronal death by protecting against neural autophagy and neuroinflammation.…”
Section: Resultsmentioning
confidence: 99%
“…As a highly selective central agonist of the α2 adrenergic receptor, dexmedetomidine has been administered in many therapeutic procedures safely and efficiently [ 6 , 7 , 8 ]. Animal studies showed that dexmedetomidine reduced neuronal death by protecting against neural autophagy and neuroinflammation, enhanced cognitive and motor recovery following traumatic brain injury, and alleviated cerebral ischemic reperfusion injury [ 9 , 10 , 11 ]. Hence, dexmedetomidine was recommended in patients after craniotomy in recent years [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Dex has been found to have myocardial protection against hypertensive hypertrophic myocardial IRI [ 34 ]. Zhao et al [ 35 ] found that Dex alleviated cerebral IRI in rats by inhibiting c-un N-terminal Kinase (JNK) pathway. Moreover, Dex reduces Nod-like receptor family pyrin domain containing 3 (NLRP3) through adenosine monophosphate-activated kinase (AMPK), thereby improving NLRP3 inflammasome activation in alveolar macrophages mediated by renal ischemia-reperfusion [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, XST can reduce neurological dysfunction and pathological damage in CI/R rats [ 21 ]. In contrast, dexmedetomidine (Dex) is an anesthesia-assisted sedative and a potent and highly selective α 2 adrenoceptor agonist [ 22 ]. Some studies have reported the neuroprotective effects of Dex in animal models of brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported the neuroprotective effects of Dex in animal models of brain injury. For instance, Zhao et al reported that Dex could relieve CI/R injury in rats by activating α 2-adrenergic receptors and blocking JNK phosphorylation and caspase-3 activation [ 22 ]. Sun et al claimed that the neuroprotective effects of Dex were achieved by suppressing spinal cord inflammation and neuronal apoptosis and alleviating spinal cord CI/R injury [ 23 ].…”
Section: Introductionmentioning
confidence: 99%